CUSTOMER SATISFACTION INDEX (CSI) PASIEN ASING TERHADAP PENYAJIAN MAKANAN DI RUMAH SAKIT KHUSUS BEDAH BIMC KUTA KABUPATEN BADUNG - Ni Kadek Putri Agustira; Anak Agung Nanak Antarini; Ni Made Dewantari (Jurnal Ilmu Gizi : Journal of Nutrition Science, 2023)
The Customer Satisfaction Index (CSI) is an index to determine the level of overall customer satisfaction with an approach that considers the importance of the product or service attributes being measured. One of the factors that determine customer satisfaction is the consumers perception of service quality which focuses on five service dimensions, are Responsiveness, Reliability, Empathy, Tangible and Assurance. The type of research that will be carried out is an observational research type with a cross sectional research design and descriptive analysis. The population of this study were all foreign patients who were hospitalized at the BIMC Kuta Special Surgery Hospital, Badung Regency, and the sample from this study was part of the population who had the following criteria, patients who were treated for at least 1 day and received regular food, man and women over the age of 18 years, are willing to be research subjects by filling out the informed consent and the patient is conscious and able to communicate. Based on the 26 samples studied, overall the patients stated that they were good with the presentation of food provided by the hospital, namely with an index of 3,412 where if this value was percentage it was already above the standard hospital satisfaction value of 85%. This is in accordance with the results of the feed back form given from the hospital to patients where in May 2021 it showed a good satisfaction value with food presentation, which was 85%.   Keywords : Customer Satisfaction Index, food presentation